Star of the Week : a story of love, adoption, and brownies with sprinkles - Friedman, Darlene (HarperCollinsPublishers, 2009)
As her turn to be "Star of the Week" in her kindergarten class approaches, Cassidy-Li puts together a poster with pictures of her family, friends, and pets, and wonders about her birthparents in China.